2021
DOI: 10.1093/humrep/deab098
|View full text |Cite
|
Sign up to set email alerts
|

How common is add-on use and how do patients decide whether to use them? A national survey of IVF patients

Abstract: STUDY QUESTION What is the prevalence and pattern of IVF add-on use in Australia? SUMMARY ANSWER Among women having IVF in the last 3 years, 82% had used one or more IVF add-on, most commonly acupuncture, preimplantation genetic testing for aneuploidy and Chinese herbal medicine. WHAT IS KNOWN ALREADY IVF add-ons are procedures, techniques or medicines which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 25 publications
0
38
1
1
Order By: Relevance
“…The S/D of women will change under too much stress and discomfort. Besides, how many acupuncture sessions should be performed for participants who suffered PER is necessary to reconsider because of the financial burden and time cost for PER ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…The S/D of women will change under too much stress and discomfort. Besides, how many acupuncture sessions should be performed for participants who suffered PER is necessary to reconsider because of the financial burden and time cost for PER ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mélange of public and private service provision appears to muddy the navigation process for patients. At the onset, patients spend a significant amount of money for baseline services, but if the process is not initially successful, patients may be more likely to purchase additional services alleged to increase fertility ( 26 , 27 ). As the journey progresses, sometimes lasting several years, the increased spending begins to act as its own source of pressure, leading to the purchase of further add-on services in hopes of a successful outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Lensen et al carried out a study in Australia among women having IVF in the previous 3 years, and they found that 82% had used one or more IVF add-on, with acupuncture, preimplantation genetic testing for aneuploidy and Chinese herbal medicine being the most common. Lensen et al also commented on the limited information about the prevalence and types of use of these add-ons [ 28 ].…”
Section: Literature Reviewmentioning
confidence: 99%